Assessment of Severe Plastic Deformation Processes in Bulk and Nanostructured Metallic Glass - Singh, Shiv Prakash; Ebrahimi, Mahmoud; Attarilar, Shokouh; Wang, Liqiang; Wang, Qudong; Djavanroodi, Faramarz (Frontiers in Materials, 2022)
The metallic glasses are known as amorphous and metastable materials. These materials have superior mechanical properties over crystalline materials with the same chemistry. Continuous efforts were made to improve the properties of metallic glass. The severe plastic deformation (SPD) method is used to improve the ductility of the glass. SPD causes the deformation at the atomic level in the disordered structure of the glass. Many methods are reported, such as cryogenic cycling, high-pressure torsion, equal channel angular pressing, etc., that are used for the SPD. In recent works on nanostructured metallic glasses, it has been evidenced that some properties, e.g., mechanical, thermal, and magnetic, have improved compared to the bulk metallic glass. This paper has reviewed the recent progress in the SPD of the bulk and nanostructured metallic glasses. Different methods for the SPD have been addressed here. The effect of SPD on the properties of metallic glass is deliberated in this paper. Moreover, the challenging tasks of deformation occurrence in the glass and its characterization were considered, trying to develop a sound understanding of SPD in bulk and nanostructured metallic glasses.